Studi Teknologi Konservasi Untuk Menurunkan Laju Erosi Pada Sub Das Sombe Lewara Provinsi Sulawesi Tengah - Edison, Edison; Bisri, M.; Suhartanto, Eri (Jurusan Teknik Pengairan, Fakultas Teknik, Universitas Brawijaya, 2012)
Sombe Lewara River area administratively at the Palu City, Sigi Regency and Donggala Regency of Central Sulawesi Province with river stream area (DAS) of 8.353,13 ha.Erosion rate about 4,329 tones/ha/year, the produced sediment of 35.520 tones/year, the class spread of land ability of class III about 46.523 ha (0.557%),class IV of 133.571 ha (1.599%), class V of 6237.1930 ha (74.669%)and class VII of 1935.843 ha (23.175%) and recommendation of land and soil conservation (RLKT) obtained that 57.60% of the Sub Das of Sombe Lewara is conservation area, buffer area of 28.75%, season plants culture /settlement area of 0.12%. Conservation simulation in vegetative obtained the average erosion decrease become 2.440 tones/ha/ years and the produced sediment become 20.770 tones/year. The sediment handling by digging at check dam.Keywords: rain, soil, slope, land usage, erosion, conservation